Analisis Eko-Efisiensi Penggunaan Recycle Water pada Industri Pengolahan Karet Alam (Studi Kasus: PT. MKC) - Amalia, Laeli Rezki; Widada, Dharma; Sukmono, Yudi (Fakultas Teknik Universitas Tulang Bawang, 2025)
The manufacturing industry in natural rubber processing uses large amounts of water resources with repeated washing processes. PT. MKC uses water resources from the river which are processed at the WTP as the main source of water for production, and uses some of the water resources in recycled water from wastewater processing to be reused in production. The selection of alternatives in improving the quality of recycled water, process of industrial wastewater treatment and the selection of domestic wastewater treatment, in the eco-efficiency analysis of the use of recycled water utilized efficiently. By using the AHP method, alternative A becomes the most advanced process of industrial wastewater treatment with a weight of 63.1%, using reverse osmosis that already exists at the WTP to process WWTP effluent water into clean water that meets the parameters of clean water for industry. Alternative PT. DUJ which offers domestic wastewater treatment technology with aeration, sedimentation, and ozonation processes is the best of domestic wastewater treatment with a weight of 53.7%. The feasibility of investment in both selected alternatives with a payment period of 2 years 5 months. Keywords: AHP, Domestic, Production, Treatment, Water